Criminological Analysis of Violence and Anarchist Demonstration Conducted by the Front Pembela Islam (FPI) Mass Organization (Ormas) - Budianto, Agus; Talia Kallista Haditama; Susento, Jovan Rafael Aurelio; Akbar, Muhamad Alief; Stefana, Violen Ester (International Journal of Law Analytics, 2024)
In a nation where the freedom of association, assembly, and expression is protected exclusively by its Constitution, Indonesia isn’t a stranger to mass organizations (Ormas) created by its citizens. With the Ormas Law, Ormas is regulated and supervised, but it doesn’t take forever for an Ormas to rebel and act by their own rules, such as the FPI Ormas. With an extensive history on violence and public disruption, this research is aimed to analyse the sociological and psychological factors behind FPI’s illegal behaviours through the eyes of criminology, and what can be done to prevent similar cases in the future. It has been found that sociology and psychology play a heavy part on influencing the illegal acts and fanatic mindset of FPI members, birthing a series of violations against the Ormas Law and even the Criminal Code. While FPI has been disbanded since 2020, it’s important to learn from the past and improve the supervision of Ormas in Indonesia to prevent the rising of another FPI.